2005
DOI: 10.1021/bi0484264
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Mechanism of a Peptide Inhibitor of HIV Reverse Transcriptase Dimerization

Abstract: The biologically active forms of human immunodeficiency viruses type 1 and 2 reverse transcriptase (RT) found in infectious virions are heterodimers. We have previously shown that the dimeric nature of reverse transcriptase represents an important target for the design of a new class of antiviral agents and have designed a short peptide (Pep-7) derived from the tryptophan-rich motif of the connection subdomain that blocks dimerization of reverse transcriptase in vitro and abolishes viral infection. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…They are found to play critical roles in viral DNA replication, in fidelity, and in drug resistance (Agopian et al, 2007;Dash et al, 2006;Depollier et al, 2005;Kim et al, 1998Kim et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…They are found to play critical roles in viral DNA replication, in fidelity, and in drug resistance (Agopian et al, 2007;Dash et al, 2006;Depollier et al, 2005;Kim et al, 1998Kim et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…wiley.com. ] dimeric conformation of the enzyme [Depollier et al, 2005]. Thus, targeting dimer stability or disruption of dimerization of HIV-1 RT provides an attractive approach for intervention in HIV-1 replication.…”
Section: Discussionmentioning
confidence: 99%
“…In protein-protein interactions the binding energy is not evenly distributed across the dimer interface but involves specific residues "hot spots" that stabilize protein complexes. We have shown that the use of small peptides targeting hot spot residues required for RT dimerization constitutes a new strategy to inhibit HIV-1 RT (16, 17) and have described a decapeptide "Pep-7"-mimicking p66/p51 interface that prevents RT dimerization by destabilizing RT subunit interactions and that blocks viral replication (23,32).…”
Section: Human Immunodeficiency Virus Type I (Hiv-1)mentioning
confidence: 99%
“…Expression and Purification of HIV-1 RT Proteins-Histagged RTs were expressed and purified as previously described (23,34). Briefly, M15 bacteria (Qiagen) were separately transformed with all the constructs of p51 and p66 subunits.…”
Section: Materials-poly(ra)-oligo(dt) and [mentioning
confidence: 99%